(untitled) (Global Journal of Human-Social Science, 2020)
Public service delivery is significant and central to building trust in the government In the era of the internet innovations in ICTs have reshaped the mode of interaction between governments and the citizens thereby affecting the delivery of public services As ICTs are providing opportunities for effective delivery of public services to the citizens an expected outcome is an improvement of trust in government by the same citizens especially in a country like Nigeria with a history of weak citizens trust in government Using an online survey conducted with 13 743 users of electronic public services in Nigeria the study found that electronic public service delivery had a significant positive effect on public trust in Nigeria The study recommended the need for improvements in some areas of electronic delivery of public services as a build-up to the observed achievements